Saving Grand Canyon : Dams, Deals, and a Noble Myth - Pearson, Byron E., 1960- (Book collections on Project MUSE., 2019)
"This book tells three interconnected stories: It chronicles a century of attempts to build dams in Grand Canyon and why those attempts failed. It demonstrates how the National Environmental Policy Act came out of these controversies. Finally, it debunks the myth that the Sierra Club saved Grand Canyon and shows how the club parlayed this perception into the leadership of the modern environmental movement after NEPA became law"--